Главный бой: [фантастический роман] / Ю. Никитин - Никитин Юрий Александрович (Княжий пир, 2006)
Экземпляры: АБ (20170620) / Инвентарный номер: 50803 / Цена: 27.20 / Авт.знак: Н 62 / ББК: 84(2Рос=Рус)6